2008
DOI: 10.1093/rheumatology/ken435
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception and muscle torque deficits in children with hypermobility syndrome

Abstract: The findings of this study demonstrated that knee joint proprioception was impaired in children with HMS. They also had weaker knee extensor and flexor muscles than healthy controls. Clinicians should be aware of these identified deficits in children with HMS, and a programme of proprioceptive training and muscle strengthening may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 34 publications
3
100
2
2
Order By: Relevance
“…This comes in agreement also with Fatoye et al, 2009 [19] who used digital myometer [MIE, Medical Research Ltd, Leeds, UK] to assess Maximum isometric knee extensor and flexor muscle torque and found that children with HMS had weaker knee extensor and flexor muscles than healthy controls.…”
Section: Discussionsupporting
confidence: 88%
“…This comes in agreement also with Fatoye et al, 2009 [19] who used digital myometer [MIE, Medical Research Ltd, Leeds, UK] to assess Maximum isometric knee extensor and flexor muscle torque and found that children with HMS had weaker knee extensor and flexor muscles than healthy controls.…”
Section: Discussionsupporting
confidence: 88%
“…When compared with healthy control subjects, JHS has been shown to have a significant impact on a wide range of outcomes, such as exercise endurance, gait, pain, proprioception, strength, function and quality of life in both children [20][21][22][23] and adults. [24][25][26][27] A recent systematic review and meta-analysis has also confirmed the impact of JHS on a range of psychological variables such as fear, agoraphobia, anxiety, depression and panic disorders.…”
Section: Fundingmentioning
confidence: 99%
“…Neural inputs derived from proprioceptive sensors are hypothesized to be crucial for the recruitment of motor units in relation to task requirements. [23] It has been shown that proprioception of the knee is reduced in EDS-HT patients, [24,25] however, the impact of proprioception on the association between muscle strength and activity limitations in EDS-HT is unknown.…”
Section: Introductionmentioning
confidence: 99%